Exploring the efficacy of laser speckle contrast imaging in the stratified diagnosis of rosacea: a quantitative analysis of facial blood flow dynamics across varied regions - Liao, Jin-Feng; Jiang, Xue-Mei; Xie, Zhen; Lei, Hua; Luo, Juan; Lv, Yu; Liu, Gang; Mao, Yujie; Song, Si-Yuan; Wang, Yi (Frontiers in Immunology, 2024)
Background: Rosacea has a high incidence, significantly impacts quality of life, and lacks sufficient diagnostic techniques. This study aimed to investigate the feasibility of Laser Speckle Contrast Imaging (LSCI) for measuring facial blood perfusion in rosacea patients and to identify differences in blood flow among various facial regions associated with different rosacea subtypes. Methods: From June to December 2023, 45 patients were recruited, with 9 excluded, leaving 36 subjects: 12 with Erythematotelangiectatic Rosacea (ETR), 12 with Papulopustular Rosacea (PPR), and 12 healthy controls. The Think View multispectral imaging analyzer assessed inflammation via grey reading values across the full face and five facial areas: forehead, nose, cheeks, and chin. LSCI measured and analyzed blood perfusion in the same areas.Plasma biomarkers IL-6, IL-1β, and TNF-α were tested in different groups.Results:Both ETR and PPR groups showed increased average blood perfusion and facial inflammation intensity by grey values compared to controls, with statistically significant differences.Average blood perfusion of ETR and PPR groups showed increased in forehead,cheeks,nose,compared to controls,and the cheeks with statistically differences between ETR and PPR.The facial inflammation intensity of ETR groups showed increased in forehead,cheeks and PPR groups showed increased in forehead,cheeks,nose and chin by grey values compared to controls,and the cheeks,nose,chin with statistically significant differences between ETR and PPR.Plasma biomarkers IL-6, IL-1β, and TNF-α were significantly elevated in both ETR and PPR groups compared to controls. Conclusion: LSCI is a valuable, noninvasive tool for assessing blood flow dynamics in rosacea, providing a data foundation for clinical research. Different rosacea subtypes exhibit distinct lesion distribution and blood flow patterns, both ETR and PPR could affecting all facial areas,particularly the cheeks in ETR and the forehead, nose, chin in PPR.